Is merit pay changing ethos in public administration? - Renato Ruffini; Giuseppe Modarelli; Roberta Sferrazzo; Matteo Turri (Cogent Business & Management, 2020)
This article aims to explore the changes in the organizational culture of public administrations following the implementation of performance-related pay-PRP systems. The work explores the switch to an explicit remuneration system through the implementation of incentives and focuses on the effects, positive or negative, this has had on the ethos of public administrations. Data from a survey carried out among private and public employees in a specific area of Southern Italy are used to analyze how the shift from an implicit to an explicit remuneration system has impacted the public servants' ethos. Due to the application of PRP, public servants are now expected to be compensated based on their performance. The ineffective management of incentives in public administrations affects the intrinsic motivation of public employees and may lead to moral disengagement. While the previous literature has focused on the practical challenges and limitations of PRP, less has been written about how PRP has changed the culture of public administrations. This article shows how PRP can change the traditional ethos of public administrations' services based on the Weberian model of bureaucracy, replacing the latter with a new one.
Keywords: 650; performance-related pay; public administration; incentives; evaluation; organizational change